2022
DOI: 10.3389/fcell.2022.883636
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Roles of Chemerin-Chemokine-Like Receptor 1 Axis in Placental Development and Vascular Remodeling During Early Pregnancy

Abstract: Chemerin is an adipokine that regulates metabolism in pregnancy. An elevation of serum chemerin level is associated with pregnancy complications. Consistently, we demonstrated that the chemerin expression was increased in placenta of preeclamptic patients at deliveries. The G protein-coupled receptor chemokine-like receptor 1 (CMKLR1) mediates the actions of chemerin. The functions of the chemerin-CMKLR1 axis in maintaining pregnancy are still unknown. In this study, we demonstrated that CMKLR1 was expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The Cmklr1-knockout mice presented histological changes indicating an increased diameter of spiral arteries and increased trophoblast invasion in the decidua but also an increased number of NK cells in the placental tissue, as well as an elevated serum IL-15 level, which is known for playing an important role in the development, survival, and activation of NK cells. On the basis of these findings, the authors concluded that chemerin and CMKLR1 are involved in the regulation of the secretion of trophoblast regulatory factors from decidual NK cells, including TNF-α, IL-10, and IL8, affecting in this way placental development and spiral artery remodeling [ 84 ]. The other study group demonstrated high levels of CMKLR1 expression by the CD56 low peripheral blood NK (pbNK) cells and observed that chemerin significantly supports pbNK cell migration through DEC and ST cells, as well as dNK cell migration through ST cells via rapid ERK activation.…”
Section: Potential Role Of Chemerin In the Pathophysiology Of Pementioning
confidence: 99%
“…The Cmklr1-knockout mice presented histological changes indicating an increased diameter of spiral arteries and increased trophoblast invasion in the decidua but also an increased number of NK cells in the placental tissue, as well as an elevated serum IL-15 level, which is known for playing an important role in the development, survival, and activation of NK cells. On the basis of these findings, the authors concluded that chemerin and CMKLR1 are involved in the regulation of the secretion of trophoblast regulatory factors from decidual NK cells, including TNF-α, IL-10, and IL8, affecting in this way placental development and spiral artery remodeling [ 84 ]. The other study group demonstrated high levels of CMKLR1 expression by the CD56 low peripheral blood NK (pbNK) cells and observed that chemerin significantly supports pbNK cell migration through DEC and ST cells, as well as dNK cell migration through ST cells via rapid ERK activation.…”
Section: Potential Role Of Chemerin In the Pathophysiology Of Pementioning
confidence: 99%
“…The role of the chemerin/CMKLR signaling pathway in placentation has begun to emerge. Recently, r-chemerin was reported to promote the syncytialization of CTBs by using the in vitro model of human choriocarcinoma BeWo cells [ 82 ]. The r-chemerin also inhibited the proliferation of dNK cells in vitro, and the conditioned medium derived from the dNK cells pre-treated with r-chemerin significantly impaired the invasion of EVTs in vitro [ 82 ].…”
Section: Roles Of the Chemerin System In Reproductionmentioning
confidence: 99%
“…Recently, r-chemerin was reported to promote the syncytialization of CTBs by using the in vitro model of human choriocarcinoma BeWo cells [ 82 ]. The r-chemerin also inhibited the proliferation of dNK cells in vitro, and the conditioned medium derived from the dNK cells pre-treated with r-chemerin significantly impaired the invasion of EVTs in vitro [ 82 ]. Meanwhile, chemerin secretion was found to be enhanced in decidualized human endometrial stromal cells, and chemerin positively regulated the chemotaxis of NK cells and angiogenesis of HUVEC cells in vitro [ 81 ].…”
Section: Roles Of the Chemerin System In Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Chemerin is involved in angiogenesis and spiral artery remodeling and might trigger delivery. 13,14 However, it may also play a role in the development of preeclampsia, given that its concentrations in blood correlate positively with the severity of preeclampsia and adverse fetal outcomes. 14,15 In agreement with this concept, placental overexpression of chemerin in pregnant mice induced a preeclampsia-like syndrome, involving high blood pressure, proteinuria, endothelial dysfunction, fetal growth restriction, and an increased sFlt-1/ PlGF ratio.…”
mentioning
confidence: 99%